BEST PROXIMITY POINT AND FIXED POINT THEOREMS IN COMPLEX VALUED RECTANGULAR b-METRIC SPACES - Yuying, T.; Sattayaporn, S.; Chantakun, W. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2024)
The aim of this paper, by using the concept of continuity of which satisfying and to defined some contraction condition of T introduced by G. Meena [12], we prove the unique best proximity point of A and fixed point of T in complex valued rectangular b-metric space. Our results extend and improve the results of G. Meena [12], and many others.